2019
DOI: 10.1016/j.dadm.2019.07.003
|View full text |Cite
|
Sign up to set email alerts
|

The Consortium for the early identification of Alzheimer's disease–Quebec (CIMA‐Q)

Abstract: Introduction The Consortium for the early identification of Alzheimer's disease–Quebec (CIMA‐Q) created a research infrastructure to recruit, characterize, and track disease progression in individuals at risk of dementia. Methods CIMA‐Q established standardized clinical, neuropsychological, neuroimaging, blood (plasma, serum, RNA, genomic DNA), cryopreserved peripheral blood mononuclear cells, and cerebrospinal fluid collection protocols. These data and biological materials are available to the research commun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 48 publications
0
36
0
Order By: Relevance
“…The study included data from the Consortium for the Early Identification of Alzheimer's disease‐Quebec cohort (CIMA‐Q http://www.cima-q.ca/en/home/). 16 The main objective of CIMA‐Q is to characterize a longitudinal observational cohort consisting of more than 350 community‐dwelling older adults recruited via advertisements, electronic media, and memory clinics from three Canadian cities (Montreal, Sherbrooke, and Quebec City). Participants were either: (1) cognitively healthy, (2) exhibiting SCD, (3) suffering from MCI, or (4) diagnosed with dementia due to probable AD.…”
Section: Methodsmentioning
confidence: 99%
“…The study included data from the Consortium for the Early Identification of Alzheimer's disease‐Quebec cohort (CIMA‐Q http://www.cima-q.ca/en/home/). 16 The main objective of CIMA‐Q is to characterize a longitudinal observational cohort consisting of more than 350 community‐dwelling older adults recruited via advertisements, electronic media, and memory clinics from three Canadian cities (Montreal, Sherbrooke, and Quebec City). Participants were either: (1) cognitively healthy, (2) exhibiting SCD, (3) suffering from MCI, or (4) diagnosed with dementia due to probable AD.…”
Section: Methodsmentioning
confidence: 99%
“…We first analyzed demographic information (age, sex, education) and baseline characterization from the cognitive reserve proxy questionnaire (CRQ) ( 31 ), ischemic index ( 32 ) and depression questionnaires [short version of Geriatric depression scale (GDS) for older adults ( 33 ) and Beck Depression Inventory II (BDI-II) for young adults]. Cognition was measured with the Montreal Cognitive Assessment (MoCA) ( 34 ) and a French version of the logical memory subtest (CIMAQ) ( 35 ) adapted from the Wechsler Memory Scale ( 36 ) using separated one-way ANOVAs with Group (three levels) as a between-subject factor.…”
Section: Methodsmentioning
confidence: 99%
“…Participants included 108 older adults from the Quebec Consortium for the early identification of Alzheimer’s disease (CIMA-Q). CIMA-Q is a multi-center collaborative research infrastructure that tracks AD progression in older adults at risk for the disease ( Belleville et al, 2019 ). The consortium has created a longitudinal cohort of older adults meeting criteria for SCD, MCI, dementia of the Alzheimer’s type (AD), and healthy controls (HC).…”
Section: Methodsmentioning
confidence: 99%
“…The study included 25 older adults with MCI, 58 older adults with SCD and 25 HC, all of whom completed the clinical, neuropsychological, and fMRI examination ( Table 1 ). All procedures of recruitment, clinical, cognitive, neuropsychiatric measures are described in Belleville et al, 2014 , Belleville et al, 2019 and can be found in Supplementary Material (S1 text) . The CIMA-Q study and this present study were approved by the Research Ethics Board of the Institut universitaire de gériatrie de Montréal.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation